A phase I/II study of sunitinib and intensive chemotherapy in patients over 60 years of age with acute myeloid leukaemia and activating FLT3 mutations. (29th March 2015) - Fiedler, Walter; Kayser, Sabine; Kebenko, Maxim; Janning, Melanie; Krauter, Jürgen; Schittenhelm, Marcus; Götze, Katharina; Weber, Daniela; Göhring, Gudrun; Teleanu, Veronica; Thol, Felicitas; Heuser, Michael; et al.
Summary Acute myeloid leukaemia (AML) with FLT3 mutation has a dismal prognosis in elderly patients. Treatment with a combination of FLT3 inhibitors and standard chemotherapy has not been extensively studied. Therefore, we instigated a phase I/II clinical trial of chemotherapy with cytosine arabinoside (Ara‐C)/daunorubicin induction (7+3) followed by three cycles of intermediate‐dose Ara‐C consolidation in 22 AML patients with activating FLT3 mutations. Sunitinib was added at predefined dose levels and as maintenance therapy for 2 years. At dose level 1, sunitinib 25 mg daily continuously from day 1 onwards resulted in two cases with dose‐limiting toxicity (DLT), prolonged haemotoxicity and hand‐foot syndrome. At dose level −1, sunitinib 25 mg was restricted to days 1–7 of each chemotherapy cycle. One DLT was observed in six evaluable patients. Six additional patients were treated in an extension phase. Thirteen of 22 patients (59%; 8/14 with FLT3–internal tandem duplication and 5/8 with FLT3‐tyrosine kinase domain) achieved a complete remission/complete remission with incomplete blood count recovery. For the 17 patients included at the lower dose level, median overall, relapse‐free and event‐free survival were 1·6, 1·0 and 0·4 years, respectively. Four out of five analysed patients with relapse during maintenance therapy lost their initial FLT3 mutation, suggesting outgrowth of FLT3 wild‐type subclones.